Processo de trabalho e produção do cuidado de enfermagem em uma instituição de apoio ao indígena - Ribeiro, Aridiane Alves (Universidade Federal de São Carlos, 2012)
This study aimed primarily to examine the workers conceptions about the process of nursing care in an institution of attention to indigenous health care. The starting point was the reference of the work process and its relation to the use of technologies in health care production. It was also considered the National Policy for the Health of Indigenous Peoples, particularly the distincted attention that should permeate the work process at the institution being studied. The empirical material was obtained from document analysis, systematic observations, guided by the flowchart Merhy Analyzer and by ten interviews with the nursing staff. A thematic analysis of categorical data was conducted and it revealed a fragmented labor process, focused on procedures and cast by institutional and bureaucratic rules. In the process of nursing work there is a clear gap from thinking to acting because planning the Schedule is a job for the responsable worker and the nursing station performs it. The worker s reports showed a sense of equality among human beings in the caring process. Therefore, it was also learned that in some situations, there is an establishment of asymetric relationship showing a certain denial of what is said. The assisted Indians in Support House are perceived by respondents as a retracted and suspicious individual. The care process should be based on a relationship based on trust. To approach the Amerindian, the nursing worker needs to undertake, especially light Technologies, empathy and affection. However, work in live action, hence the use of relational technologies, can be captured by the rigidity of the bureaucratic organizational structure. The act is cast and creative potential of workers is not valued. The caring process presents a special care, the monitoring, which is the activity of nursing staff to accompany the Indians to specialized health services outside the home support. Although the National Policy advocates a distincted attention, the work process in the institution being studied, seemed not to potentiate nor favors a care where it is considered the indigenous peculiarities of self-health care.
Keywords: Cuidados em enfermagem; Processo de trabalho; Saúde indígena; Nursing care; Work process; Indigenous health; CIENCIAS DA SAUDE::ENFERMAGEM